Integrated ecological risk assessment of dioxin compounds - Tavakoly Sany, Seyedeh Belin; Hashim, Rosli; Rezayi, Majid; Rahman, Mohammad Azizur; Razavizadeh, Bi Bi Marzieh; Abouzari-lotf, Ebrahim; Karlen, David J. (Springer Verlag (Germany), 2015)
Current ecological risk assessment (ERA) schemes focus mainly on bioaccumulation and toxicity of pollutants in individual organisms. Ecological models are tools mainly used to assess ecological risks of pollutants to ecosystems, communities, and populations. Their main advantage is the relatively direct integration of the species sensitivity to organic pollutants, the fate and mechanism of action in the environment of toxicants, and life-history features of the individual organism of concern. To promote scientific consensus on ERA schemes, this review is intended to provide a guideline on short-term ERA involving dioxin chemicals and to identify key findings for exposure assessment based on policies of different agencies. It also presents possible adverse effects of dioxins on ecosystems, toxicity equivalence methodology, environmental fate and transport modeling, and development of stressor-response profiles for dioxin-like chemicals.